2017
DOI: 10.1016/j.trecan.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Intrinsic Tumor Hotspots: Terroir for Tumorigenesis

Abstract: Epithelial tissues are highly organized systems with a remarkable homeostatic ability to maintain morphology through regulation of cellular proliferation and tissue integrity. This robust self-organizing system is progressively disrupted during tumor development. Recent studies of conserved tumor-suppressor genes in Drosophila showed how pro-tumor cells deviate from the robustly organized tissue microenvironment to take the first steps into becoming aggressive tumors. Here we review the ‘tumor hotspot’ hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…Consistently, recent studies have shown that the hinge is a hotspot in the formation of epithelial tumors (Khan et al, 2013;Tamori and Deng, 2017;Tamori et al, 2016). The results shown here provide a new example supporting the notion that the hinge is an oncogenic hotspot (Tamori and Deng, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistently, recent studies have shown that the hinge is a hotspot in the formation of epithelial tumors (Khan et al, 2013;Tamori and Deng, 2017;Tamori et al, 2016). The results shown here provide a new example supporting the notion that the hinge is an oncogenic hotspot (Tamori and Deng, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Given that miR-8 and Yki are oncogenic partners in the hinge, downregulation of miR-8 in those cells might also provide a mechanism to prevent the formation of neoplastic tumors in a context of Yki upregulation. Hinge cells in the wing disc are protected against apoptosis (a central tumor suppressor mechanism) and can survive external apoptotic inputs, including irradiation, drug-induced apoptosis and cell competition (Tamori and Deng, 2017;Tamori et al, 2016;Su, 2016, 2017). Consistently, recent studies have shown that the hinge is a hotspot in the formation of epithelial tumors (Khan et al, 2013;Tamori and Deng, 2017;Tamori et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it was shown that polyploid cells also form in Ras85D V12 /scrib −/− tumours due to CycB downregulation, and blocking their formation inhibits the invasive behaviours of these tumours (Cong et al, 2018). (6) Jun N-terminal kinase signalling can be important in tumourigenesis at transition zones -where different epithelial cell populations meet, which are often hotspots for tumourigenesis (reviewed in Tamori and Deng, 2017). One such zone occurs in the Drosophila larvae at a site where polyploid salivary gland cells meet the diploid imaginal ring cells, where tumourigenesis occurs after transient whole animal N ACT expression due to upregulation of TNF-JNK and Jak-STAT signalling (Yang et al, 2019).…”
Section: Pro-tumourigenic Jnk Signallingmentioning
confidence: 99%
“…Whilst there is evidence that wild-type epithelial cells engulf the scrib mutant dying cells [ 54 ], hemocytes play the predominant role in this process, as well as in cell competition due to variations in dMyc or ribosomal protein levels [ 145 , 146 ]. Furthermore, in tumour development, microenvironmental “hot-spots” have been revealed where the tumour has a greater chance of progressing, which has parallels with mammalian systems [ 27 , 147 ]. Molecularly, the “hot-spots” are due to endogenously higher levels of Jak-Stat signalling and the presence of a stiff basement membrane extracellular matrix, resulting in extrusion of the tumour cells apically, where they survive ( Figure 2(b) ).…”
Section: Cell Competition and Cooperating Interactions Between Celmentioning
confidence: 99%